EVALUASI KINERJA POMPA SRP PADA SUMUR X LAPANGAN K UNTUK MENDAPATKAN LAJU ALIR YANG IDEAL - Wiedya Soulisa; Erdila Indriani; Denny Ismail Pellu; Leslie S Loppies (Jurusan Teknik Mesin, 2025)
Sucker Rod Pump or also called a bobbing pump, is a tool that is often used in oil and gas wells. In well X, field K is an old well with a well depth of 750-800 ft. This well often experiences production problems, which result in decreased production rates, so it is necessary to re-identify the performance of the SRP pump. Next, you can carry out the performance calculation stage of the installed SRP pump to get the ideal flow rate in well X. Based on the calculation and evaluation results of the pump in well,771 Bpd and has a Volumetric Efficiency of 75.81%, which has achieved ideal results in that the pump's production capacity works well so that it can lift fluid to the surface optimally. Keywords: SRP, Pump Performance Evaluation, Productivity Index, Ideal flow rate